Effect of seaweed saps on growth and yield improvement of transplanted rice in old alluvial soil of West Bengal - Pramanick, Biswajit; Brahmachari, Koushik; Ghosh, Arup; Zodape, ST (Bangladesh Journal of Botany, 2014)
On summer rice, foliar spray was applied thrice at different concentrations (0, 2.5, 5.0, 7.5, 10.0 and 15.0%, v/v) of seaweed extracts (namely, Kappaphycus sp. and Gracilaria sp.) along with the recommended dose of fertilizer (RDF). The highest grain yield was recorded with the applications of 15% Kappaphykus sap + RDF, followed by 15% Gracilaria sap + RDF extract resulting in 41.47 and 34.99% increases, respectively compared to the control. The maximum straw yield was also achieved with 15% seaweed extract application. Improved nutrient uptake (N, P and K) was also observed with seaweed extract applications. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19746 Bangladesh J. Bot. 43(1): 53-58, 2014 (June)